Beyond Methodological Duality in Information and Communication Sciences: Towards a Hybridization of Qualitative and Quantitative Approaches - Ardjoun, Samir (Journal of Ecohumanism, 2026)
This paper examines the use of mixed methods within the field of Information and Communication Sciences (ICS). The adoption of a hybrid framework is presented as an operational strategy balancing investigative tools with scientific research objectives. Drawing on an interdisciplinary approach and exploring the plasticity of methodological frameworks specific to Information and Communication Sciences, this study relies on empirical feedback and interdisciplinary contributions. Our research approach explores contact zones and also aims to identify the points of convergence that link Information and Communication Sciences to other disciplines within the Humanities and Social Sciences.